Air and Surface Temperatures Differently Drive Terrestrial Carbon and Water Cycles in the High Latitudes - Jing Tang; Shouzhi Chen; David Martín Belda; Riikka Rinnan; Christian Körner; Yongshuo H. Fu (Geophysical Research Letters)
Abstract High‐latitude vegetation experience different temperatures than the ambient air temperature. While lacking a regional plant temperature product, we drove the dynamic ecosystem model, LPJ‐GUESS, with widely used ERA5‐land surface temperature (Tsurf, at radiative equilibrium) and air temperature to understand ecosystem process responses to these two temperatures. We show that tundra plants' growth is stimulated by warmer Tsurf in the summer, but in the boreal forests, colder Tsurf in the non‐summer months constrains leaf development and enzyme activity the following growing season. Tsurf drives higher productivity of tundra plant individuals but leads to less productive individuals in the boreal forest, although with compensatory changes (almost 68%) in vegetation structure. We demonstrate the importance of forcing temperature in simulating high‐latitude ecosystem processes and call for a community effort to measure plant temperatures across canopy heights and seasons to reduce uncertainties in estimating high‐latitude plant responses and feedback to climate.